Thresholds for Rural Public and Ecosystem Services: Integration into Rural Green Space Spatial Planning for Sustainable Development - Huiya Yang; Jiahui Zou; Chongxiao Wang; Renzhi Wu; Maroof Ali; Zhongde Huang; Hongchao Jiang; Fan Zhang; Yang Bai (Land)
Rural landscapes are experiencing ecosystem degradation due to urbanization and rapid suburban expansion. Ecosystem services derived from natural resources and essential public services facilitated by social capital collectively address the growingly diverse social and ecological requirements of rural residents. Even so, ecosystem services and public services are often trade-offs, highlighting the necessity to enhance their coordinated development. However, it remains unclear how to use the identified thresholds to delineate functional zones. This will scientifically guide sound and efficient spatial planning and ecological management. This study takes the suburban countryside of Jiangning in Nanjing as the study area. It explores the inclusion of the threshold value of rural public services and ecosystem services in the strategic design of sustainable suburban development in China. First, we quantify and map six types of ecosystem services (ESs) and 13 types of rural public services (RPSs). Secondly, we use the piecewise linear regression method to identify the response and threshold of 13 types of RPSs to six kinds of ESs. Finally, the combination and classification of threshold values are used to divide functional areas, and space-specific management and planning suggestions are put forward. The results are as follows (1) With the increase in RPSs, all ESs respond with a downward trend. (2) In addition to the negative linear relationship between education and social welfare services and ESs, the response thresholds of other RPSs and ESs were identified. (3) According to multiple density threshold analysis of each RPS’s response to ESs, four functional areas were obtained. We emphasize the priority of spatial planning and management, that is, the priority management of “ESs enhancement area and RPSs optimization area”. (4) The threshold values of ESs and RPSs can be used as tools to delineate functional zones and guide the spatial planning and management of rural functional areas. In general, our research helps ensure the maximization of rural ecological benefits while also meeting the growing diversity of needs of rural residents and enabling efficient, phased, gradient, and precise spatial management of suburban rural ecosystems and public services to promote the sustainable development of suburban rural areas and realize rural revitalization.